(untitled) (Revista Contexto & Saúde, 2026)
Objectives: To describe the clinical-epidemiological aspects and spatial distribution of COVID-19 in pregnant women in a municipality in the state of Maranhão, Brazil. Methods: A descriptive and ecological study with a quantitative approach, based on cases notified to the Notifiable Diseases Information System (SINAN) between May 2020 and October 2021. The variables used were: age, skin color/ethnicity, healthcare professional status, municipality of residence, street, neighborhood, signs and symptoms, comorbidities, tests performed, test completion, and case outcomes. Data were tabulated, followed by descriptive analysis, incidence calculation, and geoepidemiological analysis. The study was approved by the Research Ethics Committee of the Federal University of Maranhão under opinion No. 4,754,078. Results: 313 pregnant women were analyzed. The incidence was 64.40/1000 inhabitants. The age group most represented was 26 to 35 years, most pregnant women identified as mixed-race, and 8 were healthcare professionals. Symptoms such as fever, cough, sore throat, and dyspnea were prominent. The most frequent health conditions were diabetes and decompensated chronic respiratory diseases. Five census tracts with a significant occurrence of COVID-19 in pregnant women were identified in the municipality. Conclusions: The group most affected by COVID-19 consisted of young adult women, mixed-race, and from census tracts with low socioeconomic status. The research provides data that can assist managers in formulating prevention and assistance strategies for future health crises.